2017
DOI: 10.5301/uj.5000253
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of highly purified urofollitropin treatment in patients with idiopathic azoospermia before testicular sperm extraction

Abstract: FSH treatment showed greater efficacy rather than control by increasing the rate of PR and FR in azoospermic patients who underwent TESE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…Given that mTESE was not performed in these men, it is possible that the study results are reflective of some degree of sampling bias. Similar to previous studies, the investigators proposed the mechanism of action to be increased activity at the FSH receptor affecting both Sertoli cells and spermatogonial stem cells (4).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Given that mTESE was not performed in these men, it is possible that the study results are reflective of some degree of sampling bias. Similar to previous studies, the investigators proposed the mechanism of action to be increased activity at the FSH receptor affecting both Sertoli cells and spermatogonial stem cells (4).…”
supporting
confidence: 69%
“…Previous studies that have analyzed the effects of therapeutic FSH on sperm retrieval rates (SRR) have been limited in size, duration, randomization, presence of a control group, and inclusion/exclusion criteria (1,3,4). A nonrandomized prospective trial by Aydos et al (3) demonstrated that 75 IU of FSH administered three times weekly to azoospermic men significantly increased SRR at the time of microdissection testicular sperm extraction (mTESE) compared with control patients.…”
mentioning
confidence: 99%
“…Given the (presumed) primary testicular inability to produce sperms in such cases, there is no clear rationale in proposing a further FSH stimulation in the presence of serum FSH levels above the normal range. However, some studies reported an increased rate of sperms extracted after TESE/micro-TESE in men with non-obstructive azoospermia treated with clomiphene citrate [149], hCG [150], hMG [149], and FSH [151,152]. These findings would suggest that the minimal, residual spermatogenic activity could be stimulated even in case of elevated serum FSH levels, at least in some patients.…”
Section: Therapeutic Options To Improve Sperm Productionmentioning
confidence: 99%
“…Controlled ovarian hyperstimulation (COH) technology aims to stimulate ovulation with drugs to obtain an appropriate number of healthy fertilizable oocytes (10). The drugs commonly used in the clinic include the gonadotropin drug urofollitropin, the pituitary down-regulation medicine triptorelin acetate, and the ovarian stimulation drug hCG (11)(12)(13).…”
mentioning
confidence: 99%